2021
DOI: 10.1111/ejn.15183
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the negative impacts of aging on cognitive function; modifiable factors associated with increasing cognitive reserve

Abstract: Research suggests that social, physical, and cognitively challenging activities during lifetime, could mitigate the negative effects of aging on cognitive function. This effect is explained by the increased cognitive reserve (CR) resulting from such factors; in fact, such activities, by altering structural and functional properties of the human brain, equip one with more effective compensatory mechanisms to resist brain damage before the presentation of severe clinical symptoms. Therefore, applying appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 165 publications
1
13
0
1
Order By: Relevance
“…For example, it has been found in previous studies that people who exercise properly, have no history of cerebral infarction, do not smoke, and drink a little alcohol have a lower risk of dementia, 29 while PM 2.5 has a stronger effect in these people. Cognitive reserve is an exception 30 ; we found that people with higher cognitive reserve (associated with higher education) were less likely to be affected by PM 2.5 levels. This may be related to the fact that cognitive reserve is a part of cognitive function, and people with higher overall cognitive reserve are less likely to progress to dementia/ MCI even though their cognitive function may decline after exposure to PM 2.5 .…”
Section: Discussionmentioning
confidence: 54%
“…For example, it has been found in previous studies that people who exercise properly, have no history of cerebral infarction, do not smoke, and drink a little alcohol have a lower risk of dementia, 29 while PM 2.5 has a stronger effect in these people. Cognitive reserve is an exception 30 ; we found that people with higher cognitive reserve (associated with higher education) were less likely to be affected by PM 2.5 levels. This may be related to the fact that cognitive reserve is a part of cognitive function, and people with higher overall cognitive reserve are less likely to progress to dementia/ MCI even though their cognitive function may decline after exposure to PM 2.5 .…”
Section: Discussionmentioning
confidence: 54%
“…The hypothesis of brain reserve and cognitive reserve (CR) can be a tentative explanation of these findings. Brain reserve refers to brain volume and the number of connections among neurons, and those with younger age tended to have high brain reserve (Amanollahi et al, 2021 ). CR is believed to counter the effects of aging or brain damage, and higher education is associated with higher CR (Amanollahi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain reserve refers to brain volume and the number of connections among neurons, and those with younger age tended to have high brain reserve (Amanollahi et al, 2021 ). CR is believed to counter the effects of aging or brain damage, and higher education is associated with higher CR (Amanollahi et al, 2021 ). Individuals with high brain reserve or CR, can compensate cognitive decline (Amanollahi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is determined by several modifiable factors, including occupational attainment, engagement in leisure activities, physical activity, social engagement, or brain-challenging tasks. CR has been shown to mitigate the negative impact of aging on cognitive function and it is worth noting that there are modifiable factors that can increase it [12].…”
Section: Introductionmentioning
confidence: 99%